Sensitivity of forest phenology in China varies with proximity to forest edges - Weibin You; Ziyi Xian; Guoyi Zhou; Evgenios Agathokleous; Zhen Yu (Forest Ecosystems, 2023)
Background: Shifts in forest phenological events serve as strong indicators of climate change. However, the sensitivity of phenology events to climate change in relation to forest origins has received limited attention. Moreover, it is unknown whether forest phenology changes with the proximity to forest edge. Methods: This study examined the green-up dates, dormancy dates, time-integrated NDVI (LiNDVI, a measure of vegetation productivity in growing season), and their sensitivities to climatic factors along the gradients of distance (i.e. proximity) to forest edge (0–2 ​km) in China's natural forests (NF) and planted forests (PF). For the analysis, field-surveyed data were integrated with Moderate Resolution Imaging Spectroradiometer (MODIS) NDVI from 2000 to 2022. Results: Our results reveal that PF had earlier green-up dates, later dormancy dates, and higher LiNDVI than NF. However, green-up sensitivities to temperature were higher at the edges of NF, whereas no such pattern was observed in PF. Conversely, the sensitivity of dormancy dates remains relatively stable from the inner to the edge of both NF and PF, except for a quadratic change in dormancy date sensitivity to precipitation found in NF. Additionally, we found that the green-up sensitivity to temperature increased with decreasing proximity to edge in NF evergreen forests, while it showed the opposite trend in PF evergreen forests. Furthermore, we observed that the precipitation impact on green-up dates shifts from postponing to advancing from the inner to the edge of NF, whereas precipitation dominantly postpones PF's green-up dates regardless of the proximity to edge. The LiNDVI exhibits higher sensitivity to precipitation at the edge areas, a phenomenon observed in NF but not in PF. Conclusions: These results suggest that the responses of forests to climate change vary with the distance to the edge. With increasing edge forests, which results from fragmentation caused by global changes, we anticipate that desynchronized phenological events along the distance to the edge could alter biogeochemical cycles and reshape ecosystem services such as energy flows, pollination duration, and the tourism industry. Therefore, we advocate for further investigations of edge effects to improve ecosystem modelling, enhance forest stability, and promote sustainable tourism.